Method for industrially producing nano metal particles on large scale

By using graphene composite carbon fiber electrodes and ultrasonic vibration in a normal temperature aqueous solution, the problem of complex preparation process of metal nanoparticles and difficult to achieve industrial production in the prior art is solved, and efficient production with simple equipment, easy operation and controllable nanoparticle size is achieved.

CN119530895APending Publication Date: 2025-02-28XINHE QIYUE (CHONGQING) NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411725770.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing metal nanoparticle preparation methods are complex in technology and high in equipment configuration, making it difficult to achieve industrial mass production, and are easy to introduce impurities.

Method used

Graphene composite carbon fiber electrode was used as the cathode plate, and metal nanoparticles such as Cu, Fe, Ni, Co, Ag, Sn were prepared by electrolysis in a normal temperature aqueous solution by electrolysis.

Benefits of technology

It realizes industrial mass production with simple equipment, easy operation, and completed in room temperature aqueous solution. The nanoparticle size is controllable, the production efficiency is high, and the cost is low, making it suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005159166140000011
    Figure HDA0005159166140000011
  • Figure HDA0005159166140000012
    Figure HDA0005159166140000012
  • Figure HDA0005159166140000021
    Figure HDA0005159166140000021
Patent Text Reader

Abstract

The invention discloses a method for industrially producing nano-metal particles on a large scale, which comprises the following steps of: growing nano-metal particles on a graphene composite carbon fiber electrode in situ by adopting a direct current electroplating mode, and enabling the nano-metal particles deposited at a vertical graphene edge to fall off and sink by utilizing an ultrasonic vibration mode. The size of the metal nano-particles is controlled, the metal nano-particles fall off the surface of the electrode in time, and therefore continuous and large-batch production is achieved. The method for obtaining the nano-metal particles is carried out in a normal-temperature aqueous solution, the process is simple, energy is saved, consumption is low, and large-scale preparation of the metal nano-particles can be achieved; and no toxic or harmful gas is generated in the production process, so that the method is environment-friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of metal materials, and in particular relates to a method for industrial mass production of nano metal particles, namely a method for preparing metal nano particles by electrolysis. Background Art

[0002] Nanomaterials are extremely small in size and have a large specific surface area, which gives them special properties that many bulk materials do not have, such as small size effect, surface effect, quantum size effect, etc. Nanomaterials are the foundation of the development of nanotechnology, and therefore, the research and application of nanomaterials have developed rapidly.

[0003] Nanomaterial preparation is the most basic research work in the field of nanomaterial research. The preparation methods can be summarized as physical methods and chemical methods. Different preparation methods make the performance and size of nanoparticles different.

[0004] The physical method usually uses light and electricity technology under high temperature and high pressure conditions, vaporizes the metal through different types of heat sources, cools the atoms or molecules through the medium to form nanoparticles, and uses mechanical processes such as ball milling and spraying. No chemical changes are involved in this process. The main physical methods are thermal evaporation, sputtering and atomization. These methods are complex, nanopowders are difficult to collect, and the equipment configuration requirements are high, which is not conducive to continuous operation. The physical crushing method has a simple process and high output, but impurities are easily introduced during the preparation process.

[0005] Chemical methods include chemical precipitation, sol-gel microemulsion, high temperature and high pressure solvent thermal method, combustion synthesis, template synthesis and electrolysis. Among them, the electrolysis method can be divided into aqueous solution electrolysis and molten salt electrolysis. The metal or alloy powder produced by this method has high purity, fine particle size and low cost, which is suitable for expansion and industrial production. Summary of the invention

[0006] The purpose of the present invention is to provide a method for industrial mass production of nano metal particles, which is easy to operate, simple in device, and completed in a room temperature aqueous solution. The method uses a graphene composite carbon fiber electrode as a cathode plate, a corresponding metal salt solution as an electrolyte, and a corresponding metal as an anode plate, and electrolyzes and prepares metal nanoparticles such as Cu, Fe, Ni, Co, Ag, Sn, etc. on the surface of the cathode plate under ultrasonic vibration.

[0007] To achieve the purpose of the present invention, the following embodiments are provided.

[0008] In one embodiment of the present invention, a method for industrial mass production of nano metal particles is prepared by electrolysis, including electrolyte, cathode material and anode material, and the current density is controlled at 0.01-0.50A / cm 2, preferably 0.10-0.50A / cm 2 , more preferably 0.14-0.37A / cm 2 , wherein the electrolyte is selected from sulfate solution, nitrate solution and organic acid salt solution corresponding to metal ions, the cathode material is a graphene composite carbon fiber electrode, and the anode material is a metal single substance plate of the nano metal particles.

[0009] In some embodiments, in the method for producing nano-metal particles, the electrolyte is placed in an electrolytic cell, and the material of the electrolytic cell is acid- and alkali-resistant material, wherein the electrolyte concentration is 1%-20%, preferably 3%-6%.

[0010] In some embodiments, in the method for producing nano-metal particles, the electrolytic cell is placed in an ultrasonic vibration machine to perform ultrasonic vibration electrolysis, and the ultrasonic vibration is continuous vibration or intermittent vibration.

[0011] The interval vibration refers to ultrasonic vibration for a period of time, pausing for a period of time, vibrating again, pausing again, and repeating this process. The vibration time and interval time are sufficient to generate metal nanoparticles of target particle size on the graphene composite carbon fiber electrode. The target particle size is the particle size required for actual use. The vibration time and interval time can be adjusted according to the particle size actually required to obtain metal particles of the target particle size.

[0012] In some embodiments, the method for producing nano metal particles comprises interval vibration, such as every 10 seconds of vibration, and pausing the vibration (ie, interval) for 5-30 seconds, such as 5 seconds, 10 seconds, 20 seconds, 30 seconds, etc.

[0013] In some embodiments, in the method for producing nano-metal particles, the electrolyte temperature after the electrolysis is completed is 49-75°C.

[0014] In some embodiments, in the method for producing nano metal particles, the particle size of the metal nano particles is 10-500 nm, preferably 40-500 nm, and more preferably 40-300 nm.

[0015] In some embodiments, in the method for producing nano-metal particles, the graphene on the graphene-composite carbon fiber electrode is a vertical graphene material.

[0016] Preferably, in the method for producing nano-metal particles, the distance between the cathode material and the anode material is 1-20 cm, more preferably 5-8 cm.

[0017] Preferably, in the method for producing nano-metal particles, the electrolyte is a sulfate solution or a nitrate solution.

[0018] Preferably, in the method for producing nano metal particles, the metal is selected from Cu, Fe, Ni, Co, Ag and Sn.

[0019] In a specific embodiment, an industrialized method for mass production of nano-metal particles of the present invention adopts an electrolytic method, comprising an ultrasonic vibrator, an electrolytic cell, an electrolyte, a cathode plate and an anode plate, wherein the electrolyte includes but is not limited to a sulfate, nitrate or organic acid salt solution corresponding to the metal ion, the cathode plate is a graphene composite carbon fiber electrode, and the anode plate is a metal plate of the same element as the nano-metal particles. The specific operation steps include:

[0020] 1) Add electrolyte into the electrolytic cell and vertically insert the cathode and anode into the electrolytic cell;

[0021] 2) adjusting the distance between the cathode plate and the anode plate to 1-20 cm, preferably 5-8 cm;

[0022] 3) placing the electrolytic cell in an ultrasonic vibrator, connecting the metal plate and the graphene composite carbon fiber electrode to the positive and negative electrodes of a DC power supply respectively, and turning on the ultrasonic vibrator;

[0023] 4) Electrolysis: DC power supply set to constant voltage working mode, current density 0.10A-0.40A / cm 2 , more preferably 0.14-0.37A / cm 2 ;

[0024] 5) During the electrolysis process, metal ions are deposited on the graphene tips of the graphene composite carbon fiber electrode to generate solid particles, which fall off from the electrode surface under the action of ultrasound and gradually sink to the bottom;

[0025] 6) After the electrolysis is completed, the solid particles at the bottom are separated by filtration, washed with deionized water and dried to obtain metal nanoparticles.

[0026] In the above specific embodiment, the graphene composite carbon fiber electrode is obtained by in-situ growth of upright graphene sheets on a carbon fiber substrate by direct current plasma enhancement.

[0027] In the above specific implementation scheme, the ultrasonic vibration is an interval vibration, such as 10 seconds of vibration and 5-30 seconds of pause, such as 5 seconds, 10 seconds, 20 seconds, 30 seconds, etc. In other words, the ultrasonic interval vibration time refers to the vibration time and the interval time sufficient to generate the metal nanoparticles of the target particle size on the graphene composite carbon fiber electrode. The so-called target particle size refers to the particle size distribution of the metal nanoparticles according to actual needs, and the interval vibration time is adjusted according to actual needs to obtain the metal nanoparticles of the desired particle size.

[0028] In the above specific embodiment, the particle size of the solid particles generated on the graphene tip of the graphene composite carbon fiber electrode is 10-500nm.

[0029] Compared with the existing metal nanoparticle preparation method, the method of the present invention has the following advantages:

[0030] 1. The equipment is simple, the operation is simple, it is completed in a room temperature aqueous solution, no toxic or harmful gases are produced, and it is friendly to the environment and personnel.

[0031] 2. Continuous production is possible. Nanoparticle preparation can be completed continuously by simply adding new positive plates.

[0032] 3. The size of nanoparticles is controllable, and the selective growth of target size of nanoparticles can be achieved by adjusting the electroplating current and the ultrasonic vibration time and interval.

[0033] The method of the present invention is characterized in that: using graphene composite carbon fiber electrode as cathode plate, utilizing graphene edge and active site, and generating metal nanoparticles by electricity, because graphene itself has high specific surface area, and ultrasonic vibration can quickly grow nanoparticles, which greatly improves production efficiency and reduces industrial cost. During electrolysis, the weak connection between graphene tip and metal enables the generated nanoparticles to desorb from the electrode surface under ultrasonic vibration and deposit in the electrolyte, reducing the agglomeration effect, obtaining finer nanoparticles, and easily separating from the electrolyte, realizing industrial production. Therefore, the method of the present invention mainly utilizes ultrasonic vibration to make the nano-metal particles deposited at the edge of vertical graphene fall off and precipitate, and by controlling ultrasonic wave and / or ultrasonic interval vibration, the size of metal nanoparticles is controlled, and metal nanoparticles fall off the electrode surface in time, thereby realizing continuous and large-scale commercial production. Compared with the existing preparation method of metal nanoparticles, the method of the present invention is conducive to the rapid and inexpensive production of metal nanoparticles, providing a low-cost and low-pollution metal nanoparticle product for the research of metal nanoparticles, and has broad commercial prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 It is a schematic diagram of a device for preparing nano-metal particles by direct current electrolysis at room temperature according to the present invention;

[0035] Figure 2 is a scanning electron microscope image of the graphene composite carbon fiber electrode used in the method of the present invention;

[0036] Figure 3 The figure is a scanning electron microscope image of metal nanoparticles prepared by the method of the present invention.

[0037] In the figure: 1- DC regulated power supply; 2- cathode plate; 3- electrolyte; 4- anode plate; 5- electrolytic cell; 6- nanometal. DETAILED DESCRIPTION

[0038] The following examples are merely representative and are used to further understand and illustrate the essence of the present invention, but are not intended to limit the scope of the present invention in any way.

[0039] Unless otherwise specified, conventional reagents and materials used in the following examples can be obtained from commercial sources.

[0040] For example, copper plates, nickel plates and iron plates are all commercially available products.

[0041] The graphene composite carbon fiber electrode used is a self-made new cathode (refer to patent CN 111155302 for preparing cathode materials, which is introduced for reference).

[0042] The square acid- and alkali-resistant container used is 30cm*20cm*20cm in length, width and height respectively.

[0043] The power supply used is Uni-T UDP3305S high-precision DC regulated power supply.

[0044] The cleaning machine used is Fuyang F300PLUS industrial ultrasonic cleaning machine.

[0045] The prepared metal nanoparticles were analyzed by SEM.

[0046] Example 1 Preparation of copper metal nanoparticles

[0047] Schematic diagram of the device for preparing nano-metal particles by direct current electrolysis at room temperature Figure 1 shown.

[0048] The cathode material is graphene composite carbon fiber (see Figure 2 ), electrode plate area 25cm 2 The end where graphene is grown faces the anode, and this end is the surface where metal nanoparticles are generated.

[0049] The anode is a single metal plate such as copper, and the electrolysis area is 25cm 2 .

[0050] Using the above device, the nano metal particles are prepared by electrolysis according to the following steps.

[0051] The anode plate 4 to be used is polished with sandpaper and ultrasonically cleaned to remove surface impurities and oil stains. The cathode plate 2 is a graphene composite carbon fiber electrode.

[0052] A copper sulfate electrolyte 3 with a concentration of 3% is prepared in a container, the solution volume is about 6L, there is no precipitation in the solution, and after the copper sulfate is completely dissolved, it is poured into an electrolytic cell 5, in which an ultrasonic vibrator (not shown) is provided.

[0053] Insert the cathode plate 2 and the anode plate 4 into the electrolytic cell 5, install and fix them, control the distance between the electrodes to 5 cm, and start the ultrasonic vibrator.

[0054] Connect the graphene composite carbon fiber electrode cathode plate 2 to the negative electrode of the DC stabilized power supply 1, and connect the metal copper plate to the positive electrode of the DC stabilized power supply 1. Turn on the DC stabilized power supply 1, set it to constant voltage mode, the voltage limit is 4V, press the switch to start electrolysis. Under this electrolysis condition, the electrolysis time is 90min, and the current density is 0.2A / cm 2 , the final temperature of the electrolyte is 52°C.

[0055] The precipitate in the electrolyte was filtered and washed with ultrapure water to obtain clean nanometal 6, namely copper nanoparticles. After vacuum drying, the particles weighed 0.60 g.

[0056] The particle size of the product detected by SEM is 150-300nm. Figure 3 .

[0057] Example 2 Preparation of copper metal nanoparticles

[0058] The device and method are the same as in Example 1, except that:

[0059] 1) The initial copper sulfate solution concentration is 6%;

[0060] 2) Adjust the ultrasonic vibration interval to 10 seconds of vibration and 30 seconds of rest;

[0061] 3) After the electrolysis, the temperature of the electrolyte rises to 73°C, and the average current density is 0.37A / cm 2 ;

[0062] 4) The precipitate was filtered and washed with ultrapure water to obtain clean copper nanoparticles. After vacuum drying, the weight of the copper nanoparticles was 1.11 g.

[0063] SEM detected that the particle size was 400-500nm.

[0064] Example 3 Preparation of copper metal nanoparticles

[0065] The device and method are the same as in Example 1, except that:

[0066] 1) Set the voltage limit of the DC regulated power supply to 3V;

[0067] 2) The copper sulfate content of the electrolyte is 6%, and the distance between the electrodes is changed to 8 cm;

[0068] 3) After the electrolysis, the electrolyte temperature is 63°C and the average current density is 0.24A / cm 2 ;

[0069] 4) The precipitate was filtered and washed with ultrapure water to obtain clean copper nanoparticles, which were then vacuum dried to obtain particles weighing 0.72 g.

[0070] The particle size determined by SEM is 100-300 nm.

[0071] Example 4 Preparation of Copper Metal Nanoparticles

[0072] The device and method are the same as in Example 1, except that:

[0073] 1) Set the DC regulated power supply voltage limit to 3V;

[0074] 2) Adjust the ultrasonic vibration interval to 10 seconds of vibration and 20 seconds of rest;

[0075] 3) The distance between electrodes was changed to 8 cm;

[0076] 4) After the electrolysis, the electrolyte temperature is 49°C and the average current density is 0.14A / cm 2 ;

[0077] 5) After the precipitate is washed with ultrapure water, clean copper nanoparticles are obtained. After vacuum drying, the obtained particles weigh 0.42 g.

[0078] The average particle size detected by SEM is 40-100 nm.

[0079] Example 5 Preparation of Iron Metal Nanoparticles

[0080] The device and method are the same as in Example 1, except that:

[0081] 1) The electrolyte is FeSO4, wherein the concentration of the electrolyte is 3%;

[0082] 2) The cathode plate is an iron sheet;

[0083] 3) After the electrolysis, the temperature of the electrolyte rises to 54°C, and the average current density is 0.18A / cm 2 ;

[0084] 4) The precipitate was separated and washed with ultrapure water to obtain clean iron nanoparticles. After vacuum drying, the obtained particles weighed 0.53 g.

[0085] SEM detected the particle size to be 50-100 nm.

[0086] Example 6 Preparation of Iron Metal Nanoparticles

[0087] The device and method are the same as in Example 5, except that:

[0088] 1) The initial FeSO4 solution concentration is 6%;

[0089] 2) Adjust the ultrasonic vibration interval to 10 seconds of vibration and 30 seconds of rest;

[0090] 3) After the electrolysis, the temperature of the electrolyte rises to 70°C, and the average current density is 0.32A / cm 2 ;

[0091] 4) The precipitate was separated and washed with ultrapure water to obtain clean iron nanoparticles. After vacuum drying, the obtained particles weighed 0.97 g.

[0092] SEM detected that the particle size was 100-200nm.

[0093] Example 7 Preparation of Iron Metal Nanoparticles

[0094] The device and method are the same as in Example 5, except that:

[0095] 1) Set the voltage limit of the DC regulated power supply to 3V;

[0096] 2) Adjust the ultrasonic vibration interval to 10 seconds of vibration and 30 seconds of rest;

[0097] 3) The FeSO4 content of the electrolyte is 6%, and the distance between the electrodes is changed to 8 cm;

[0098] 4) After the electrolysis, the electrolyte temperature is 63°C and the average current density is 0.24A / cm 2 ;

[0099] 5) The precipitate was separated and washed with ultrapure water to obtain clean iron nanoparticles. After vacuum drying, the obtained particles weighed 0.72 g.

[0100] SEM detected the particle size to be 70-120 nm.

[0101] Example 8 Effect of vibration interval time and current density on the particle size of metal nanoparticles

[0102] According to the electrolysis device and method of the embodiment, the relevant parameters are changed as shown in the following table to examine the effects of vibration interval time and current density on nanoparticles. The vibration is performed for 10 seconds and then paused (interval) for 5, 10, and 20 seconds. Under the same vibration interval condition, the current density is changed to prepare metal nanoparticles and the particle size distribution is observed. The results are shown in Tables 1 and 2 below.

[0103] Table 1. Effect of vibration interval on the particle size distribution of metal nanoparticles

[0104] Vibration interval Current density Solution concentration Pole spacing Particle size distribution 5s <![CDATA[0.37A / cm 2 ]]> 6% 5cm 75~90nm 10s <![CDATA[0.37A / cm 2 ]]> 6% 5cm 140~200nm 20s <![CDATA[0.37A / cm 2 ]]> 6% 5cm 300~450nm

[0105] Table 2. Effect of vibration current density on the particle size distribution of metal nanoparticles

[0106] Vibration interval Current density Solution concentration Pole spacing Particle size distribution 20s <![CDATA[0.24A / cm 2 ]]> 6% 5cm 100~150nm 20s <![CDATA[0.37A / cm 2 ]]> 6% 5cm 300~450nm 20s <![CDATA[0.45A / cm 2 ]]> 6% 5cm 800~1200nm

[0107] From the experimental results in Tables 1 and 2 above, it can be observed that the ultrasonic vibration interval time and the current density directly affect the particle size distribution of the metal nanoparticles. The preparation parameters can be adjusted according to actual needs to obtain nano-metal particles with corresponding particle size distribution.

Claims

1. A method for industrial mass production of nano metal particles, characterized in that: It is prepared by electrolysis, including electrolyte, cathode material and anode material, and the current density is controlled at 0.01-0.50A / cm 2 , preferably 0.10-0.50A / cm 2 , more preferably 0.14-0.37A / cm 2 , wherein the electrolyte is selected from sulfate solution, nitrate solution and organic acid salt solution corresponding to metal ions, the cathode material is a graphene composite carbon fiber electrode, and the anode material is a metal single-substance plate of nano-metal particles.

2. According to the method of claim 1, the electrolyte is placed in an electrolytic cell, the material of the electrolytic cell is acid- and alkali-resistant material, and the electrolyte concentration is 1%-20%, preferably 3%-6%.

3. The method according to claim 2, wherein the electrolytic cell is placed in an ultrasonic vibration machine for ultrasonic vibration electrolysis, and the ultrasonic vibration is continuous vibration or intermittent vibration.

4. The method according to claim 3, wherein the interval vibration, the vibration time and the interval time are sufficient to generate metal nanoparticles of target particle size on the graphene composite carbon fiber electrode; preferably, the ultrasonic wave vibrates for 10 seconds each and the interval is 5-30 seconds.

5. The method according to claim 4, wherein the electrolyte temperature is 49-75°C after the electrolysis is completed.

6. The method according to claim 1 or 5, characterized in that: The particle size of the metal nanoparticles is 10-500 nm, preferably 40-500 nm, more preferably 40-300 nm.

7. According to the method of claim 1, the graphene on the graphene composite carbon fiber electrode is an upright graphene material.

8. The method according to claim 1, wherein the distance between the cathode material and the anode material is 1-20 cm, preferably 5-8 cm.

9. The method according to claim 1, wherein the electrolyte is a sulfate solution or a nitrate solution.

10. The method according to claim 1, wherein the metal in the nano metal particles is selected from Cu, Fe, Ni, Co, Ag and Sn.